American Colossus : The Triumph of Capitalism, 1865-1900 - Brands, H. W. (New York : Anchor Books, 2011)
Chronicle of how a few wealthy businessmen reshaped America from a land of small farmers and small businessmen into an industrial giant.
Keywords: Capitalists and financiers -- United States; History -- 19th century; Capitalism -- United States; History -- 19th century; United States -- Economic conditions -- 19th century; United States -- Social conditions -- 19th century; Nonfiction